(untitled) (Global Journal of Human-Social Science, 2022)
This study focuses on the massive reception of refugees in Chad in a context of both civil and asymmetric wars These refugees mostly coming from Sudan Central African Republic and to a lesser extent Nigeria have found refuge in most cases in the border area subject to recurring insecurity However the Chadian government and its humanitarian partners somehow manage to protect and secure the refugee camps But the massive arrival of asylum seekers has revealed the absence of legal and structural framework to host this population of refugees The technical and financial support of humanitarian partners has made it possible to innovate in asylum laws and in the setting up of such institutions This collaboration resulted in an alignment of government policy with that of humanitarian organizations in favor of refugees from the civil war But the direct involvement of Chad in 2015 in the war against violent Islamism in Nigeria gave rise a concern of security and stigmatizing approach towards Nigerian refugees assimilated to Boko-haram Consequently we are witnessing a difference in treatment between what can now be called refugee from the civil war and refugee from the asymmetric war The first continues to benefit from various programs aimed at integrating it into the local socio-economic fabric While the second is being pushed back from urban areas and confined to militarized refugee camps on the borders of Lake Chad